2011
DOI: 10.1111/j.1442-2050.2011.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic relevance of p21WAF1 in stage III esophageal squamous cell carcinoma

Abstract: The prognostic effect of p21(WAF1) expression on esophageal squamous cell carcinoma patients is controversial. Further clarifying the effect of this protein is beneficial for optimizing the patient outcomes. In the current study, we investigated the expression of p21(WAF1) protein in 189 specimens of stage III ESCC by immunohistochemistry. As shown by the Kaplan-Meier curve, the overall survival rate of the positive-expression group was significantly higher than that of the negative-expression group (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Our results were consistent with those reports implying the positive prognostic role of elevated p21 expression in ESCC. 7,8,[10][11][12][13] However, several other reports suggested an adverse prognostic role of up-regulated p21 expression for ESCC patients. 5,6,9 The inconsistency among these studies is most likely due to inadequate study design, limited populations with different geographic locations, or even different esophageal cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with those reports implying the positive prognostic role of elevated p21 expression in ESCC. 7,8,[10][11][12][13] However, several other reports suggested an adverse prognostic role of up-regulated p21 expression for ESCC patients. 5,6,9 The inconsistency among these studies is most likely due to inadequate study design, limited populations with different geographic locations, or even different esophageal cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Even though p21 is best known for its cyclin-dependent kinase inhibitory function, this protein also can inhibit apoptosis, which might account for its oncogenic activities [20,41]. Most of the studies suggested that p21 is present at the nucleus when considered as a tumor suppressor, and at the cytoplasm when considered as an oncogene [20].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA alkylating agents induce the phosphorylation and activation of p53, leading to an increase in p21 expression [6]. Thus, p21 may suppress tumors by its function in mediated p53-dependent G1 growth arrest [20]. Despite this, paradoxical oncogenic effects have been linked to p21, especially by its anti-apoptotic activity [27,41].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have identified that CDKN1A overexpression in cancer tissues is associated with tumor aggressiveness and poor survival: Dai et al (29) suggested that CDKN1A expression in breast cancer tissues was correlated with LNM and poor survival of patients with breast cancer, and increased MDA-MB231 breast cancer cell migration and invasion via transforming growth factor β-mediated mothers against decapentaplegic homolog 3 acetylation. In addition to the aforementioned studies (4,(22)(23)(24)(25)(26)(27), there have been other investigations indicating that low expression of CDKN1A in various cancer tissues is associated with poor prognosis (30,31). The molecular mechanism by which different CDKN1A expression levels affect prognoses in patients with different types of cancer remains unclear and requires additional investigation.…”
Section: Discussionmentioning
confidence: 99%